1986
DOI: 10.1289/ehp.866673
|View full text |Cite
|
Sign up to set email alerts
|

Acute symptoms following exposure to grain dust in farming.

Abstract: History of acute symptoms (cough, wheezing, shortness of breath, fever, stuffy nose, and skin itching/rash) following exposure to grain dust was obtained from 661 male and 535 female current and former farmers. These symptoms were relatively common: 60% of male and 25% of female farmers reported at least one such symptom on exposure to grain dust. Association of cough, wheezing, shortness of breath, and stuffy nose with skin reactivity and capacity to form IgE is consistent with an allergic nature of these sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Results of the present study show that, on the average, there were few farmers who accumulated more than 2 months of exposure to grain dust per year, and even this occurred intermittently. It also shows that the previously reported [Manfreda et al, 1986;Darke et al, 19761 frequent acute symptoms in farmers on exposure to grain dust do not produce accumulative damage. Thus, grain farmers can be reassured that the acute symptoms may be a nuisance, but they do not constitute a reason to quit farming because of fears of future permanent disability.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Results of the present study show that, on the average, there were few farmers who accumulated more than 2 months of exposure to grain dust per year, and even this occurred intermittently. It also shows that the previously reported [Manfreda et al, 1986;Darke et al, 19761 frequent acute symptoms in farmers on exposure to grain dust do not produce accumulative damage. Thus, grain farmers can be reassured that the acute symptoms may be a nuisance, but they do not constitute a reason to quit farming because of fears of future permanent disability.…”
Section: Discussionsupporting
confidence: 72%
“…It is important to determine if farming and grain exposure are associated with an increased prevalence of chronic respiratory disorders, since this could have implications for prevention. A hypothesis that grain exposure increases the risk for respiratory disorders in farmers is reasonable, for studies of grain elevator workers have suggested, although not consistently, an association between grain dust and chronic respiratory symptoms and lower values of lung function [Tse et al, 1973;do Pic0 et al, 1977;Broder et al, 1979;Chan-Yeung et al, 1980;Cotton et al, 1983;Manfreda and Warren, 19841. In addition, acute respiratory symptoms occur frequently in grain-exposed farmers, suggesting that grain dust can provoke a biologic reaction [Manfreda et al, 1986;Darke et al, 1976;James et al, 19861. A long-term effect of such a reaction is a possibility.…”
Section: Introductionmentioning
confidence: 99%
“…Shoveling or grinding grain, or cleaning out grain storage structurescanalsoexposefarmerstobacterialandfungalspores and byproducts. Respiratory reactions include hypersensitivity pneumonitis (''farmer's lung''), toxic organic dust syndrome (TODS) similar to that caused by inhalation of grain dusts (''grain fever''), and confinement house dusts, chronic bronchitis, acute bronchitis, asthma, and irritation of the nose and sinuses [Manfreda et al, 1986;Cormier et al, 1993;Lacasse et al, 1997;Simpson et al, 1998;Bharadwaj et al, 1999;Melenka et al, 1999;von Essen et al, 1999;Kirkhorn and Garry, 2000;Schuyler et al, 2000]. Use of nuisance dust masks, dust/mist masks, powered air-purifying respirators, safety goggles, steel-toed footwear, and heavy gloves are all recommended for this work.…”
Section: Discussionmentioning
confidence: 99%
“…
Inhalation of grain dust is known to cause respiratory symptoms in farmers and grain elevator workers [doPico et al, 1987;Dosman et al, 1987;Manfreda et al, 1986]. To study the inflammatory changes present in the lower respiratory tract of symptomatic grain farmers, bronchoscopy and bronchoalveolar lavage (BAL) were performed at harvest and again at a time of low grain dust exposure.
…”
mentioning
confidence: 99%